A scientific note on the detection of honeybee viruses using real-time PCR (TaqMan) in Varroa mites collected from a Thai honeybee (Apis mellifera) apiary - Chantawannakul P. (2014)
Bee parasitic mite syndrome is a disease complex of colonies simultaneously infested with Varroa destructor mites and infected with viruses and accompanied by high mortality. By using real-time PCR (TaqMan), five out of seven bee viruses were detected in mite samples (V. destructor) collected from Thailand. Moreover, the results of this study provide an evidence for the co-existence of several bee viruses in a single mite. This is also the first report of bee viruses in mites from Thailand.